Expression of Immune-Related Genes of Ducks Infected with Avian Pathogenic Escherichia coli (APEC) - Li, Rong; Li, Ning; Zhang, Jinzhou; Wang, Yao; Liu, Jiyuan; Cai, Yumei; Chai, Tongjie; Wei, Liangmeng (Frontiers in Microbiology, 2016)
Avian pathogenic Escherichia coli (APEC) can cause severe disease in ducks, characterized by perihepatitis, pericarditis and airsacculitis. Although the studies of bacteria isolation and methods of detection have been reported, host immune responses to APEC infection remain unclear. In response, we systemically examined the expression of immune-related genes and bacteria distribution in APEC-infected ducks. Results demonstrated that APEC can quickly replicate in the liver, spleen and brain, with the highest bacteria content at 2 day post infection. The expression of Toll-like receptors (TLRs), avian β-defensins (AvBDs) and major histocompatibility complex (MHC) were tested in the liver, spleen and brain of infected ducks. TLR2, TLR4, TLR5 and TLR15 showed different expression patterns, which indicated that they all responded to APEC infection. The expression of AvBD2 was upregulated in all tested tissues during the 3 days of testing, whereas the expression of AvBD4, AvBD5, AvBD7 and AvBD9 were downregulated, and though MHC-I was upregulated on all test days, MHC-II was dramatically downregulated. Overall, our results suggest that APEC can replicate in various tissues in a short time, and the activation of host immune responses begins at onset of infection. These findings thus clarify duck immune responses to APEC infection and offer insights into its pathogenesis.